2016
DOI: 10.3390/nu8120763
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Sleep Protein Ingestion to Improve the Skeletal Muscle Adaptive Response to Exercise Training

Abstract: Protein ingestion following resistance-type exercise stimulates muscle protein synthesis rates, and enhances the skeletal muscle adaptive response to prolonged resistance-type exercise training. As the adaptive response to a single bout of resistance exercise extends well beyond the first couple of hours of post-exercise recovery, recent studies have begun to investigate the impact of the timing and distribution of protein ingestion during more prolonged recovery periods. Recent work has shown that overnight m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
94
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(95 citation statements)
references
References 44 publications
1
94
0
Order By: Relevance
“…The food items used for each training block were oat bars (PurePower, Denmark), dried fruit (System Frugt A/S, Denmark), fruit bars (The Whole Company Food A/S, Denmark), fruit juice (PURE, Harboe, Denmark), and protein water (Arla MOVE, Arla, Denmark). Before sleep, all participants ingested 20 g of PRO, 1.3 g of CHO, and 2.1 g of FAT from a commercially available powder (Arla MOVE, Arla) to facilitate protein synthesis and recovery overnight …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The food items used for each training block were oat bars (PurePower, Denmark), dried fruit (System Frugt A/S, Denmark), fruit bars (The Whole Company Food A/S, Denmark), fruit juice (PURE, Harboe, Denmark), and protein water (Arla MOVE, Arla, Denmark). Before sleep, all participants ingested 20 g of PRO, 1.3 g of CHO, and 2.1 g of FAT from a commercially available powder (Arla MOVE, Arla) to facilitate protein synthesis and recovery overnight …”
Section: Methodsmentioning
confidence: 99%
“…Before sleep, all participants ingested 20 g of PRO, 1.3 g of CHO, and 2.1 g of FAT from a commercially available powder (Arla MOVE, Arla) to facilitate protein synthesis and recovery overnight. 28 To detect whether total food intake differed between groups, all participants recorded individual food and fluid intake for 4 days before and during the intervention (Madlog, Denmark). Of these 4 days, 1 day was a weekend day to ensure inclusion of a day independent of a training block.…”
Section: Dietary Recording and Timing Of Carbohydrate Intakementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was shown that pre-sleep protein ingestion in older individuals is successfully digested, absorbed and incorporated in de novo protein synthesis during the overnight period [15]. Thus, the overnight period, which under normal circumstances is linked to postabsorptive muscle catabolism, could be used to maximise muscle anabolism with important implications in sarcopenia [16,17]. In addition to the potential for overnight muscle anabolism, pre-sleep protein ingestion has been reported to increase next morning resting metabolic rate (RMR) and fat oxidation, potentially conferring beneficial changes in body composition over time [18].At present, the effect of pre-sleep protein ingestion on next morning appetite and metabolic health parameters in older individuals is unclear.…”
mentioning
confidence: 99%
“…For example, early work by Bergstrom and Hultman demonstrated that an intravenous glucose infusion reduced muscle glycogen breakdown by ~20% during 60 min of cycling [5]. While many subsequent studies have observed a lower rate of muscle glycogen utilization when carbohydrate was ingested during prolonged exercise [9,[41][42][43][44][45][46], others have failed to confirm these findings [47][48][49][50][51]. For example, Coyle et al observed an increase in time to fatigue when subjects ingested carbohydrate during exercise compared to a placebo, despite no differences in muscle glycogen utilization between the treatments [47].…”
Section: Carbohydrates During Exercise As An Ergogenic Aidmentioning
confidence: 99%